Task complexity reveals expertise of table tennis players - Padulo, Johnny; Pizzolato, Fabio; Tosi Rodrigues, Sergio [UNESP]; Migliaccio, Gian Mario; Attene, Giuseppe; Curcio, Raffaele; Zagatto, Alessandro M. (My University, 2016)
BACKGROUND: The purpose of this study was to examine the effect of intensive practice in table tennis on perceptual, decision-making and motor-systems. Groups of elite (HL, N.=11), intermediate (LL, N.=6) and control players (CC, N.=11) performed tasks of different levels. METHODS: All subjects underwent to reaction time test and response time test consisting of a pointing task to targets placed at distinct distances (15 and 25 cm away) on the right and left sides. Only the HL and LL groups were requested to perform the ball speed test in forehand and backhand condition. RESULTS: In the CC group reaction time was higher compared to the HL (P<0.05) group. In the response time test, there was a significant main effect of distance (P<0.0001) and the tennis table expertise (P=0.011). In the ball speed test HL players were consistently faster compared to LL players in both forehand stroke (P<0.0001) and backhand stroke (P<0.0001). Overall, the forehand stroke was significantly faster than the backhand stroke. CONCLUSIONS: We can conclude that table tennis players have shorter response times than non-athletes and the tasks of reaction time and response time are incapable to distinguish between the performance of well-trained table tennis players and that of intermediate players, but the ball speed test seems to be able to do it.
Keywords: Motor control laterality; Reaction time; Task performance and analysis; Technical expertise